(untitled) (Progressive Agriculture, 2014)
Unpuddled transplanting of rice is gaining attention in Bagnaldesh agriculture. Energy budget is essential for efficient management of the resources in agricultural production. The energy balance under different minimum tillage practices in rice cultivation was assessed during 2009-11 by comparing the parameters: energy input, energy output, energy productivity and energy output:input ratio. Energy input in CT, SPWT, BP and ST were 25.50, 23.15, 20.48 and 20.49 GJ ha-1, respectively in rice cultivation. Maximum energy was consumed for chemical fertilizers. Tillage energy ranked second in conventional tillage and ranked fourth in minimum tillage options. Energy output was insignificant due to insignificant yield difference. Unpuddled transplanting (BP and ST) showed 8-12% increase in energy productivity and 22-24% increase in energy output:input ratio. However, from the energy saving point of view, unpuddled transplanting may be considered better options depending on the resources availability in rice cultivation. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19176 Progress. Agric. 24(1&2): 229 - 237, 2013